2017
DOI: 10.1093/neuonc/nox116
|View full text |Cite
|
Sign up to set email alerts
|

CD70, a novel target of CAR T-cell therapy for gliomas

Abstract: These studies identify a previously uncharacterized and ubiquitously expressed immunosuppressive ligand CD70 in GBMs that also holds potential for serving as a novel CAR target for cancer immunotherapy in gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 36 publications
5
118
0
Order By: Relevance
“…Cell lines engineered to produce soluble CD70 increase proliferation and IFN secretion of cocultured lymphocytes. 45 Treating in vivo murine glioma models with both a CD70 specific CAR T therapy 46 and a CD70 antibody-drug conjugate produced tumor regression. 47 However, other studies have suggested that the CD27 pathway may actually suppress T lymphocytes.…”
Section: Cd27mentioning
confidence: 99%
“…Cell lines engineered to produce soluble CD70 increase proliferation and IFN secretion of cocultured lymphocytes. 45 Treating in vivo murine glioma models with both a CD70 specific CAR T therapy 46 and a CD70 antibody-drug conjugate produced tumor regression. 47 However, other studies have suggested that the CD27 pathway may actually suppress T lymphocytes.…”
Section: Cd27mentioning
confidence: 99%
“…106 All of these antigens are overexpressed in glioblastoma patient specimens, and CAR-T cells targeting them reduce glioblastoma growth in mouse models. One major area of study is the identification and validation of new target antigens, including chondroitin sulphate proteoglycan 4 (CSPG4), 104 podoplanin 105 and CD70.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…One major area of study is the identification and validation of new target antigens, including chondroitin sulphate proteoglycan 4 (CSPG4), 104 podoplanin 105 and CD70. 106 All of these antigens are overexpressed in glioblastoma patient specimens, and CAR-T cells targeting them reduce glioblastoma growth in mouse models. [104][105][106] Combinatorial approaches are also being explored through the development of CAR-T cells which recognise more than one target antigen.…”
Section: Route Of Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Additional antigens that have been proposed as GBM-associated targets for CAR T cells include EphA2, 8 chondroitin sulfate proteoglycan 4 (CSPG4), 2,11 podoplanin (PDPN), 31 the cancer stem cell antigen CD133, 35,36 and the immune-suppressive ligand CD70. 16 Clinical data are not yet available for CAR constructs targeting these antigens, though several are currently under investigation.…”
Section: Numerous Modifications and Improvements Of Existingmentioning
confidence: 99%